Concomitant infestation of Toxocara cati and Ancylostoma tubaeforme in a mongrel cat - Saravanan, M. (J Parasit Dis, 2014)
A 3½ years old mongrel female cat was brought with the history of inappetence, seizure and lateral recumbency since 4 days and motion sickness since 2 days. Faecal examination confirmed Toxocara cati and Ancylostoma tubaeforme along with un-hatched live Toxocara cati larvae. Treatment has been initiated with Pyrantel pamoate and along with supportive therapy.